Government versus opposition: Who should be who in the 16th German Bundestag? - Dinko Dimitrov; Claus-Jochen Haake (Bielefeld University, Institute of Mathematical Economics (IMW), 2005)
We model the process of coalition formation in the 16th German Bundestag as a hedonic coalition formation game. In order to induce players' preferences in the game we apply the Shapley value of the simple game describing all winning coalitions in the Bundestag. Using different stability notions for hedonic games we prove that the 'most' stable government is formed by the Union Parties together with the Social Democratic Party.
urn:nbn:de:hbz:361-8217
Keywords: D72; C71; 330; Coalition formation; Shapley value; Simple games; Winning coalitions; Regierungswechsel; Regierungskoalition; Parlament; Shapley-Wert; Deutschland